Non-Lévy Mobility Patterns of Mexican Me’Phaa Peasants Searching for Fuel Wood - Souza, Og de; Miramontes, Octavio; Hernández, Diego; Ceccon, Eliane (Human Ecology, 2012)
We measured mobility patterns that describe walking trajectories of individual Me’Phaa peasants searching for and collecting fuel wood in the forests of “La Montaña de Guerrero” in Mexico. These 1-day excursions typically follow a mixed pattern of nearly-constant steps when individuals displace from their homes towards potential collecting sites and a mixed pattern of steps of different lengths when actually searching for fallen wood in the forest. Displacements in the searching phase seem not to be compatible with Lévy flights described by power-laws with optimal scaling exponents. These findings, however, can be interpreted in the light of deterministic searching on heavily degraded landscapes where the interaction of the individuals with their fuel wood-scarce environment produces alternative searching strategies than the expected Lévy flights. These results have important implications for future management and restoration of degraded forests and the improvement of the ecological services they may provide to their inhabitants.
Keywords: Lévy flights; Human mobility; Deterministic walks; Me’Phaa; Fuel wood; Ecological restoration; Foraging Mexico